The Effect of Project-Based Learning on Students' Mathematics Learning in Indonesia: A Systematic Literature Review - Annisa Wahidatul Asmi; Fainida Rahmat; Mazlini Adnan (International Journal of Education, Information Technology, and Others, 2022)
Project-based Learning (PjBL) is one of the learning models relevant to the Indonesian 2013 Curriculum which emphasizes developing 21st century skills. Hence, the aim of this study was to perform a systematic literature reviews (SLR) concerning the effect of the PjBL model on students' mathematics learning in Indonesia. The reporting of this SLR is in accordance with the standards of the Preferred Reporting Items for systematic reviews and Meta-Analyses (PRISMA) statement. Article searches through database, namely Scopus and Google Scholar, found 44 articles after being filtered according to the established criteria. The finding showed the effect of PjBL model on learning achievement, higher order thinking skills, conceptual understanding, learning motivation, creative thinking skills, and critical thinking skills. The findings also revealed that most of the studies employed quasi-experimental, pre-experimental, action research, and case studies as research design and PjBL module as learning materials. Additionally, majority of the studies were carried out for the mathematics topics such as statistics, linear equations, and geometry. Further PjBL studies are needed in other mathematics topics as well as their effect on other variables.